Stress in pintado (Pseudoplatystoma corruscans) during farming procedures - Fagundes, Michele [UNESP]; Urbinati, Elisabeth Criscuolo [UNESP] (Elsevier, 2008)
Pintado (Pseudoplatystoma corruscans) is a piscivorous catfish and one of the most important farmed fish in Brazil. However, there is a paucity of information on the stress physiology of the species. To understand how pintado respond physiologically to stressors commonly encountered in intensive rearing, the present study submitted juvenile fish to capture (chasing, netting and air exposure), 12-h transport, or prolonged (24 h) exposure to light or darkness and then measured blood indicators of stress. After capture, blood cortisol peaked within 30 min and returned to resting values within 60 min, whereas glucose peaked within 30 min and remained at those levels until 24 h after capture. Blood chloride tended to decrease after capture and osmolality was lowest 60 min and 24 h after capture. Hematocrit and erythrocyte number (RBC) decreased until 48 h after capture, when sampling ceased. Cortisol decreased after 12-h transport, especially at 48 h, and glucose showed the same pattern. Chloride and osmolality did not change after transport. Hematocrit peaked 12 h after the arrival, and RBC and hemoglobin had the same profile. After 24 h exposure to light or darkness, blood cortisol and glucose tended to decrease but chloride and osmolality did not change because of the high variation among individuals. Hematocrit, RBC and hemoglobin were highest immediately after the light or dark regime. These hormonal, metabolic, ionic and hematological responses suggest that pintado behaves as the majority of fish species when facing an acute stress but that in a more prolonged stressful situation its physiological responses are dependent on its metabolic features of oxidative preference to supply the metabolic cost of physical disturbance. © 2008 Elsevier B.V. All rights reserved.
Keywords: Brazilian catfish; Capture; Photoperiod; Transport